Newly established stem cell transplant program: 100 days follow-up of patients and its comparison with published Indian literature - Aseem Kumar Tiwari; Dinesh Arora; Ravi C Dara; Pranav Dorwal; Nitin Sood; Ruchira Misra; Sunil Kumar Gupta; Vimarsh Raina; Ashok Kumar Vaid (Indian Journal of Medical and Paediatric Oncology)
Background: Hematopoietic progenitor stem cell transplantation (HPSCT) is used as a standard treatment option to improve outcome in hematological and nonhematological disorders. It is important for new HPSCT program to look at its patient outcome data and compare it with the published data to evaluate the efficacy of program. Aims: The aim was to compile and collate the patient outcome data of HPSCT and compare with published reports. Materials and Methods: Patient demographics, indications, stem cell harvest by apheresis, dose collected, infusion, engraftment, and follow-up data were collected from hospital information system from 2010 to 2013 in a tertiary care hospital. HPSCs were mobilized with granulocyte colony-stimulating factor, and harvests were done on the 5th day. Engraftment was decided for neutrophil when counts were 0.5 × 109/L and for platelets when counts were 20 × 109/L on two consecutive days without any transfusion support. Results: There were 133 harvests for 95 patients with various disorders; multiple myeloma was most common in autologous and acute lymphoblastic leukemia in allogeneic group. One hundred harvests were done for autologous and 33 for allogeneic HPSCT. In autologous group, of 66 patients, 60 (90.9%) received stem cell infusion at median dose of 4.63 × 106 CD34+ cells/kg. Similarly, in allogeneic group, of 29 patients, 27 (93.10%) received infusion at median dose of 5.8 × 106 CD34+ cells/kg. 58 (96.9%) patients and 25 (92.6%) engrafted in autologous and allogeneic group, respectively. The median time for neutrophils engraftment was 11 days in autologous group and 12 days in allogeneic group. The median time for platelet engraftment was 11.5 days in autologous group and 13 days in allogeneic group. The 100-day survival rate was 95% (n = 57) in autologous group and 77.8% (n = 21) in allogeneic group. Conclusion: This data analysis shows reasonably good results of HPSCTs with majority of patients surviving at 100-day follow-up.